Strategi Peningkatan Mutu Perguruan Tinggi Agama Islam (PTAI) - Erlina Farida (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2009)
This article focuses on strategy that might be applied by Islamic Higher Education as part of National Higher Education-which up to this time still walking for behind it-to increase its quality. Some strategies written on this paper are the up to date of higher education, approaches like market based approach, learning organization, customer loyalty, service quality, entrepreneurship, commitment, etc., that hopefully able to become the strategies to increase the quality of Islamic Higher Education in Indonesia.